ANALISIS PENYETARAAN JABATAN ESELON IV SEBAGAI FUNGSIONAL DI PEMERINTAH KOTA SEMARANG TAHUN 2025 - Rayhan Sausan Royan Putraloka; Rina Martini (Journal of Politic and Government Studies, 2026)
National bureaucratic simplification encourages the equalization of structural positions into functional positions in order to streamline organizational structures and strengthen the merit system. This study aims to analyze the implementation of the equalization of Echelon IV positions within the Semarang City Government and its implications for task arrangement and organizational workflow. This research employs a descriptive qualitative method conducted in Semarang City. Informants were drawn from the Regional Civil Service, Education and Training Agency (BKPP) and the Organizational Bureau of the Regional Secretariat. Data were collected through interviews, observations, and documentation, and analyzed through data reduction, data presentation, and conclusion drawing using an organizational management approach. The results show that bureaucratic simplification is implemented through the 1Mahasiswa Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Diponegoro 2Dosen Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Diponegoro elimination of Echelon IV structural positions and their equalization into functional positions, resulting in a more streamlined organizational structure. However, several Echelon IV positions remain in accordance with criteria set by the Ministry of Home Affairs, while the role of the Work Team Leader facilitates coordination despite the absence of a specific compensation mechanism.